A Comparison of Screening Instruments: Predictive Validity of the BESS and BSC. (December 2014) - King, Kathleen R.; Reschly, Amy L.
The purpose of this study was to evaluate and compare two behavior screening instruments—the Behavioral and Emotional Screening System and the Behavior Screening Checklist. The sample consisted of 492 elementary school children from the southeastern United States. The psychometric properties of the screening instruments were evaluated in terms of intra-rater agreement, concurrent validity, and predictive validity of academic and behavioral outcomes. Results revealed that both screeners were significantly correlated with behavioral and academic variables. Consumers of screening instruments are encouraged to select an instrument that has sound psychometric properties and is practical for use in applied settingsC.